Direct Health Care Costs, Health Services Utilization, and Outcomes of Biliary Atresia: A Population-based Cohort Study. Issue 4 (April 2020) - Siddiq, Shabnaz; Jimenez-Rivera, Carolina; Kuenzig, M. Ellen; Lima, Isac; Geraghty, Michael T.; Ng, Vicky L.; Tam, Karen; Benchimol, Eric I.
ABSTRACT: Objectives: Biliary atresia (BA) is the most common reason for liver transplant in childhood, and outcomes worsen with older age at hepatoportoenterostomy (HPE). We determined direct health care costs in children with BA, compared to controls in a population-based cohort of children in Ontario, Canada. Methods: We used health administrative data to identify all children diagnosed with BA between 2002 and 2016 (n = 121) and matched controls (n = 602). We determined annual direct healthcare costs, and rates of health services utilization, liver transplantation, death, portal hypertension, cirrhosis, esophageal varices, and major upper gastrointestinal bleeding requiring hospitalization. Multivariable regression models determined the association between age at HPE, risk of liver transplant, and direct costs. Results: Incidence of BA was 6.07 (4.99–7.15) per 100, 000 live births. The annual median (interquartile range) direct health care costs were higher in BA cases ($4210; interquartile range $1091–$16, 765) compared to controls ($283; $112–$634). Compared to age at HPE <45 days, there was no significant association between direct costs and HPE ≥90 days (rate ratio 1.24, 95% confidence interval [CI] 0.78–1.97) or 45 to 90 days (rate ratio 1.05, 95% CI 0.73–1.50). Age at HPE ≥90 days was significantly associated with risk of undergoing liver transplant compared to age <45 days (hazard ratio 5.27, 95% CI 2.45–11.34). Direct costs were higher in patients with BA who underwent liver transplantation compared to those who did not ($39, 476±$84, 367 vs $22, 579 ± $67, 913). Conclusions: Direct ealth care costs were high in patients with BA, especially in those who underwent liver transplantation. Age at HPE was associated with risk of liver transplantation, but not direct health care costs, utilization, or other risk outcomes. Abstract : Supplemental Digital Content is available in the text